Dropped head syndrome due to myogenic atrophy --- a case report of surgical treatment - Ishidou Yasuhiro; Yamamoto Takuya; Abematsu Masahiko; Zenmyo Michihisa; Komiya Setsuro; Ijiri Kosei (BMC, 2011)
Abstract We report a case of a 69-year-old man with dropped head syndrome associated with isolated neck extensor myopathy (INEM). Over a period of 2 years, he exhibited progressive inability to lift his chin off his chest, resulting in the dropped head position that impaired his activities of daily living. He had a disturbed gait with severe imbalance of spinal alignment. Computed tomography revealed osseous contracture of cervical vertebral bodies in flexed position. Anterior combined posterior reconstruction surgery yielded a successful outcome in his activities of daily living, including his walking balance of spinal alignment. Pathologic study confirmed myogenic atrophy in the cervical extensor muscles. We suggest that consideration for surgical management should be given to dropped head syndrome especially due to INEM.